THE EFFECTIVENESS OF GROUP COUNSELING SERVICES USING THE WDEP TECHNIQUE IN IMPROVING STUDENT LEARNING DISCIPLINE AT SMP NEGERI 7 PALU - Fitriani, Dian; Musafir, Devi Erawati (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to assess how effective the reality group counseling service using the WDEP technique is in improving student learning discipline at SMP Negeri 7 Palu. In this study, the Quasi-Experimental Design method is used. The research data were processed and analyzed using descriptive and inferential analysis using the Mann-Whitney formula at a 95% confidence level (= 0.05). The experimental group's average pre-test score after receiving the WDEP reality group counseling service was 69.31, while the control group was 68.89. The experimental group's average post-test score was 81.11, while the control group was 75.56. At 0.045 0.05, the Mann-Whitney test was found to be significant. In this research, the Mann-Whitney test results revealed that H0 was rejected and H1 was accepted. The reality group counseling service using the WDEP technique is effective in improving student learning discipline at SMP Negeri 7 Palu, according to the findings of this study.